Bahraini and Non‑Bahraini Women in Bahrain’s Workforce - Sharon Nagy (Arabian Humanities)
This paper describes the parallel entry of Bahraini and non‑Bahraini women into the workforce and explores the intersections of gender, work and nationality in Bahrain, as well as local variations in the globalizing work force. The research provides both a sociocultural and historical contextualization to women’s entry into the workforce. The patterns of gender and nationality characterizing Bahrain’s workforce today are to be situated within an economic and social framework which has undergone many changes since the early 20th century. Now, within a context where Bahraini women are encouraged and motivated to seek employment, does the employment of foreign women help or hinder their entry into the work force? And in a cultural context where certain occupations have long been viewed as unsuitable for women, does foreign women employing impact cultural perceptions of these jobs? These questions are asked of occupations in which relatively large numbers of women work, namely education, hospitality, retail and household work.